Methotrexate use and NAD+/NADH metabolism in psoriatic keratinocytes - Liszewska, Agata; Robak, Ewa; Bernacka, Małgorzata; Bogaczewicz, Jarosław; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Methotrexate inhibits tetrahydrofolic acid production and influences mitochondrial oxygen uptake and activity of several enzymes in the respiratory chain reactions, which utilize nicotinamide adenine dinucleotide-linked (NAD-linked) substrates. Hyperproliferation of keratinocytes in psoriasis requires oxidative phosphorylation, in which the reduced form of nicotinamide adenine dinucleotide (NADH) is an electron donor. One hypothesis links increased cellular metabolism to the increased NADH/NAD+ ratio; as expected, the topical application of NAD+ (oxidized form of nicotinamide-adenine dinucleotide) resulted in a clinical improvement of psoriatic lesions in one study. Nevertheless, another report revealed reduced fluorescence of NADH in psoriatic plaques. The biological activity of NADH is not limited only to serving as the electron donor. It was also found to regulate gene transcription.